Assessment of the Hybrid Education Learning Program (HELP) of the AHEAD Learning Platform of San Pablo Colleges - Ortega, Araceli; Velecina, Josefina; Lunar, Bernardo (JPAIR Institutional Research, 2021)
The distinctive strategy for learning continuity in the High School Department of San Pablo Colleges (SPC) during this pandemic is the Hybrid Education Learning Program (HELP). The descriptive study determined the self-efficacy for hybrid learning among selected Junior and Senior High School learners in SPC (n=917). The study also probed into learners’ perceptions of hybrid learning in relation to the interdependence of modular and online learning. The results showed that students were generally positive about hybrid learning, and they also acknowledge the interdependencies between modular and online learning. The majority of the students (82%) regard themselves with high self-efficacy for online learning. Students are one in saying (99.67%) that they can submit online assignments well.  Moreover, the majority of the students (78%) regard themselves with high self-efficacy for modular learning, but unlike in submitting online assignments (99.67%), students claim that a relatively lower percentage (65.31%) can submit offline assignments easily. The indicators with the least percentages of agreeing with the online and modular learning statements say that they can use the library’s online resources and focus on schoolwork when faced with distractions.  It is also evident that students still wish to be in the same room with their teacher and classmates based on the relatively low percentages of agreeing to the statements.
Keywords: Education; hybrid learning; modular distance learning; online learning; learning continuity; descriptive design; Philippines